Psychotropic drug utilization in psychiatric outpatient department of a tertiary care teaching hospital in India - Mudhaliar, Mohanraj Rathinavelu; Ghouse, Ishrar Shaik Mohammad; Sadubugga, Priyanka; Narala, Swaroop Reddy; Chinnakotla, Vidyasagar; Yendluri, Prabhakar (International Journal of Research in Medical Sciences, 2017)
Background: Although psychotropic medications have had a remarkable impact on psychiatric practice that legitimately can be called revolutionary, their utilization and consequences on real life effectiveness and safety in actual clinical practice need continuous study. Methods: The current retrospective study of six months’ duration was designed to assess the utilization of antipsychotics and its prescribing pattern in a tertiary care hospital of south India, which included prescriptions of patients suffering from a psychiatric illness with at least one psychotropic drug of all ages and both sexes. Results: Out of 150 cases reviewed, 46% were of schizophrenia, where male (60.67%) at higher incidence of psychiatric illness, and maximum patients were under the age group of 29-39 years (54.67%). In present study of 355 prescribed drugs 72.67% were psychotropic medications. As per World Health Organization/International Network for Rational Use of Drugs (INRUD) drug use indicators average number of drugs per prescription (2.37%), average number of psychotropic drugs per prescription (1.72%), psychotropic drugs prescribed as Fixed Dose Combinations (FDCs) was 26.36%, and percentage of drugs prescribed by generic name (91.08%). In our study, 48.09% of psychotropic drugs were utilized in the treatment of schizophrenia, diazepam (17.06%) was the only psychotropic medication distributed in the management of all three observed psychiatric disorders and the study showed a higher utilization of psychotropic drugs as FDCs (25.98%) in the management of schizophrenia. Conclusions: The study advocated an overall rational utilization of psychotropic drugs with a fewer deviations due to socio-economic status of patients and prescription practices of healthcare providers.